2012
DOI: 10.4141/cjps2011-149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fungicide, seeding date and seedling age on clubroot severity, seedling emergence and yield of canola

Abstract: Hwang, S. F., Cao, T., Xiao, Q., Ahmed, H. U., Manolii, V. P., Turnbull, G. D., Gossen, B. D., Peng, G. and Strelkov, S. E. 2012. Effects of fungicide, seeding date and seedling age on clubroot severity, seedling emergence and yield of canola. Can. J. Plant Sci. 92: 1175–1186. The infestation of seeds by Plasmodiophora brassicae can result in the transmission of clubroot disease in canola. Five fungicides, including Dynasty 100 FS (azoxystrobin), Helix Xtra (thiamethoxam+difenoconazole+metataxyl+fludioxonil), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…In contrast, resting spore populations decline under continuous fallow or repeated cropping of a resistant cultivar at a rate equivalent to a half-life of 4.4 years, which was slightly longer than that observed in Sweden (Wallenhammar, 1996). This difference may be associated with the shorter growing season and cooler conditions during the growing season in Alberta (Hwang et al, 2012b).…”
Section: Baiting Cropsmentioning
confidence: 74%
See 1 more Smart Citation
“…In contrast, resting spore populations decline under continuous fallow or repeated cropping of a resistant cultivar at a rate equivalent to a half-life of 4.4 years, which was slightly longer than that observed in Sweden (Wallenhammar, 1996). This difference may be associated with the shorter growing season and cooler conditions during the growing season in Alberta (Hwang et al, 2012b).…”
Section: Baiting Cropsmentioning
confidence: 74%
“…Similarly, early seeding of canola can reduce clubroot severity and increase yield, although emergence may also be reduced (Hwang et al, 2012b). Cool soil temperatures (< 12 • C or 14 • C) prevent or slow the development of the pathogen.…”
Section: Seeding Datementioning
confidence: 96%
“…As a result, a range of alternative management strategies has been assessed for their usefulness in canola production, including early seeding (Hwang et al ., ), biological control (Peng et al ., ) and bait crops (Ahmed et al ., ). Studies on the impact of bait crops on soil resting spore populations and subsequent clubroot severity showed that resting spore populations were often slightly reduced following two cycles of cruciferous crops (canola or Chinese cabbage) relative to non‐cruciferous host crops such as perennial ryegrass ( Lolium perenne ) or non‐host crops such as spring cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotation is one of the most important cultural techniques recommended to control soilborne diseases of many crops. In greenhouse trials it was found that cropping resistant canola has a slightly greater effect on the reduction of P. brassicae resting spore populations than incorporating a fallow period (Hwang et al ., , ). Another study revealed that spore populations decreased by an order of magnitude when there was a 2‐year interval between canola crops, indicating a potential for the management of spore populations through crop rotation (Peng et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Infection of the Brassicaceae family with the obligate biotrophic pathogen Plasmodiophora brassicae Woronin, a cercozoan protist belonging to the class phytomyxea, results in the development of root galls (clubroots) and consequent stunting of plants [3], [4]. Clubroot disease has been reported in more than 60 countries resulting in overall reduction in the yield of canola by about 10–15% [5].…”
Section: Introductionmentioning
confidence: 99%